Giardia microti in pet Microtus guentheri: Evidence of a parasite never detected in Italy. (February 2021) - De Liberato, Claudio; Montalbano Di Filippo, Margherita; Sagrafoli, Daniele; Ferraro, Davide; Guadano Procesi, Isabel; Berrilli, Federica
Abstract: The genus Giardia includes several species distinguished by morphological, biological and molecular features. Currently, eight species within the genus are retained as valid. In Italy no identification of Giardia species other than Giardia duodenalis has been so far reported. Fecal samples were collected from two Günther's Voles ( Microtus guentheri ) positive to Giardia cysts by microscopic investigation and immunofluorescence. The voles were born in Milan (Northern Italy) from two gravid females imported from the Netherlands and kept for sale in a pet shop in Varese (Northern Italy). Positive feces were subjected to a nested PCR to amplify a 18S rRNA fragment for molecular characterization. A phylogenetic analysis was conducted to compare the obtained sequence with those of all other Giardia species available in GenBank for the 18S locus, using the Maximum Likelihood (ML) method by R software. Sequence analyses unambiguously identified the isolates as belonging to G. microti, showing 99% of identity with those of its isolates available in GenBank. A well-defined cluster, supported by significant bootstrap values and corresponding to the G. microti cluster, including sequences obtained from M. guentheri, was evidenced in the ML tree, confirming species assignment. The present finding represents the first report of G. microti from pet animals in Italy. Graphical abstract: Unlabelled Image Highlights: Giardia microti is for the first time reported from Italy. Giardia microti was introduced in Italy from abroad in pet Microtus guentheri. International pets trade is confirmed to be a way of introduction of new pathogens. Possible spill over of Giardia microti to wild native hosts can't be ruled out.